Victorian Alpine Plot Network: Plot Details for Lowland-to-highland Roadside Transects 4WD Track Data, South-East Highlands, Australia - John Morgan (TERN Australia, 2015)
This Victorian Alpine Plot Network Road Transects 4WD Track Data Package comprises spatial and elevation data for 5 Lowland-to-highland 4WD Roadside Transects in the South-East Highlands, Australia. Plots are located at attitudinally stratified intervals along five attitudinally-stratified transects. The transects follow major roads and management tracks in the Victorian Alps. Each track is divided into 20 altitudinal sectors in which a single plot is situated. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.